The Complete Metasploit Guide : Explore Effective Penetration Testing Techniques with Metasploit. - Rahalkar, Sagar (Packt Publishing, Limited, 2019)
This Learning Path is your one-stop solution to learn everything that is required to validate your complex system with penetration testing. Starting with the architecture of the Metasploit framework, this Learning Path shows how to leverage the many features and functionalities of Metasploit to perform thorough penetration testing and secure ...